2019
DOI: 10.1161/strokeaha.118.022180
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Low Ankle-Brachial Index on the Risk of Recurrent Vascular Events

Abstract: Background and Purpose— Low ankle-brachial index (ABI) identifies a stroke subgroup with high risk of recurrent stroke, cardiovascular events, and death. However, limited data exist on the relationship between low ABI and stroke in low and middle-income countries. Therefore, we evaluated the prevalence of ABI ≤0.90 (which is diagnostic of peripheral artery disease) in nonembolic stroke patients or transient ischemic attack and assessed the correlation of low ABI with stroke risk, factors, and recur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…In recent years, with the continuous development of vascular function research and the update of technology, noninvasive function detection indicators reflecting vascular aging have gradually been used in clinical and scientific research. At present, a large number of studies have confirmed that early detection of flow-mediated dilation (FMD), [3] brachial ankle pulse wave velocity (baPWV) [4] and ankle brachial index (ABI) [5] are important strategies to slow down vascular aging. In…”
Section: Functional Evaluation Of Vascular Agingmentioning
confidence: 99%
“…In recent years, with the continuous development of vascular function research and the update of technology, noninvasive function detection indicators reflecting vascular aging have gradually been used in clinical and scientific research. At present, a large number of studies have confirmed that early detection of flow-mediated dilation (FMD), [3] brachial ankle pulse wave velocity (baPWV) [4] and ankle brachial index (ABI) [5] are important strategies to slow down vascular aging. In…”
Section: Functional Evaluation Of Vascular Agingmentioning
confidence: 99%
“…ABI is also the most commonly used indicator of changes in the function and structure of peripheral arteries in vascular surgery. Several studies have pointed out that ABI can be used to predict the severity of coronary artery disease [ 8 , 9 ]. However, there are few studies using carotid IMT and ABI to evaluate the severity of coronary artery disease in children with KD.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies evaluated the prognostic effect of PAD in all stroke or non-cardioembolic stroke patients ( 24 , 25 ). However, the prognostic value of PAD in CE is not fully understood.…”
Section: Discussionmentioning
confidence: 99%